Machaerium opacum Vogel (Fabaceae): phytochemical study and toxicity to Atta sexdens Linnaeus (Hymenoptera: Formicidae) - Santos, Renato Gomes; da Silva Júnior, Weber Martins; Duarte, Geane Karla Gonçalves Ferreira; Cunha, Gracielle Oliveira Sabbag; da Silva, Daniela Moreira; de Oliveira, Amanda Aparecida [UNESP]; Bueno, Odair Correa [UNESP]; Menezes, Antônio Carlos Severo (Taylor & Francis, 2021)
In this work was described the phytochemical investigation of Machaerium opacum Vogel (Fabaceae) leaves as well as the insecticidal activity of its crude extract and fractions against Atta sexdens Linnaeus (Hymenoptera: Formicidae). The phytochemical study led to the identification of α-amyrin, β-amyrin, lupeol, phytol, isomucronulatol and rutin, described for the first time in M. opacum and mucronulatol. Insecticidal activity was assessed by the ingestion of the crude extract and fractions incorporated into an artificial diet at three different concentrations (0.2, 1.0 and 2.0 mg mL−1). Statistical analysis revealed that all the samples of M. opacum at all concentrations tested showed significant results when compared to the pure diet control.
Keywords: Insecticidal activity; leaf-cutting ant; toxicological bioassays